Identification of MYC/BCL2 double-expressers lymphomas in diffuse large B cell lymphoma patients and association with their prognostic parameters and survival rates: a single centre experience - Ahmad, Aliza; Abd Ghani, Fauzah; Jaafar, Junalina; Abdullah, Maizaton Atmadini (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Diffuse large B cell lymphoma (DLBCL) is a heterogenous disease some of which show co-expression of c-MYC and BCL2 and they are known as double expressers (DE) lymphoma. DE lymphoma has been shown to be associated with aggressive clinical course and poor outcome in comparison to those without co-expression. The as- sociation of DE lymphomas with their prognostic parameters and the overall survival rate of DE compared to non-DE lymphoma patients were investigated. Method: 66 formalin-fixed paraffin-embedded DLBCL cases were subjected to c-MYC and BCL2 immunohistochemical staining. Results: Out of 66 cases, 25(37.9%) cases showed c-MYC and BCL2 co-expression. Majority of the patients were in age category of  60 years (68.0%). Male and female distribu- tion were almost equal. DE lymphoma was significantly associated with ABC subtype in comparison to GCB subtype (p= 0.026). Median survival time for DE was 29 months and non-DE was 34 months. Log rank analysis showed there was no significant difference in the overall survival rate of DE and non-DE patients (p=0.401). Conclusion: This study showed significant association between DE lymphomas and ABC subtype. Identification of DE lymphoma with ABC subtype may guide the clinicians in identifying patients with poorer outcome hence a more aggressive treatment may be offered to this group.